Projeto e implantação de uma unidade de encapsulação pela tecnologia SAILA - Cavassa, Arthur Fagundes (2021)
Nanotechnology offers new usages for materials and products, either due to their small size scale, allowing a better dissolution and penetration, or due to the change in its properties. When it is necessary to protect compounds, extend life or enhance their transportation, the encapsulation technique emerges as a strong and effective alternative. Based on these concepts, nanocapsules shows different advances in the delivery, formulation and applicability of the most diverse products. Supercritical Assisted Injection in a Liquid Antissolvent (SAILA) is a technique that derives from Supercritical Antisolvent (SAS) technology, and it is intended for the formation of nanocapsules. Through the use of pumps and heat exchangers, contact is promoted between a fluid in the supercritical state (FSC) and a pre-prepared organic phase. The result is a liquid that, directed to an injector, is expanded in a vessel containing anti-solvent liquid, acting as a driving force for the atomization and formation of the capsules. In this context, this work aims to design and implement a pilot unit of the SAILA process. Initially, a process flow chart was proposed, followed by the dimensioning and acquisition of vessels, pipes, connections, valves and other necessary accessories. To validate the equipment, α-bisabolol nanocapsules in a polymeric lactic acid (PLA) coating were produced and analyzed using scanning electron microscopy (SEM) and dynamic light scattering (DLS), resulting in spherical nanocapsules with a size of 169,4 ±3,5 nm and zeta potential of -25,3 ±0,816 mV, in average. The samples were carried out in triplicate, showing a coefficient of variation of 2,06% for size and 3,22% for zeta potential, indicating that the prepared nanocapsules shows stability and reproducibility. The resulting equipment will act as an instrument of innovation and technology in the production of nanoparticles, leading to a series of new studies in the academic area.